On the identity of Isoperla curtata (Plecoptera: Perlodidae): behavioural and molecular approaches show the existence of two separate species - de Figueroa, José Manuel Tierno; Gaetani, Brunella; Luzón-Ortega, Julio Miguel; López-Rodríguez, Manuel Jesús; Fochetti, Romolo (Zootaxa, 2011)
The identity of Isoperla curtata Navás, 1924, an Iberian endemic, has been questioned since its description. Marked variability in pigmentation, wing length, penial armature and ecology of populations have been noted. To clarify the taxonomic status of I. curtata we examined variation in mating calls and cytochrome c oxidase subunit I sequences for two populations from north-central and southern Spain. Results of both approaches support the presence of two species. The north-central population corresponds to the nominal taxon, I. curtata, while southern populations represent a new species, Isoperla morenica, described herein.